2017
DOI: 10.1007/s10517-017-3687-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Factors on Mobilization of Mesenchymal Stem Cells

Abstract: We studied mobilization of bone marrow stem cells the under conditions of boost-therapy with granulocytic CSF and erythropoietin. Immunophenotyping of the peripheral blood was carried out in patients after transplantation of tissue-engineered trachea during the perioperative period. We observed an increase in hemopoietic stem cell pool and appearance of multipotent mesenchymal stromal cells in systemic circulation, their maximum concentration being recorded on days 10-14 after surgery. These data indicated a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The effect of growth factors on MSC mobilization remains controversial. While MSCs were isolated from the mobilized PB by some authors (Fernandez et al ., ; Zvaifler et al ., ; Gilevich et al ., ), others failed to reproduce similar findings (Wexler et al ., ; De Felice et al ., ). Recent data suggests that although G‐CSF could increase MSCs in the BM, neither G‐CSF alone or in combination with plerixafor affects the PB mobilization of MSCs (De Felice et al , ).…”
Section: Discussionmentioning
confidence: 85%
“…The effect of growth factors on MSC mobilization remains controversial. While MSCs were isolated from the mobilized PB by some authors (Fernandez et al ., ; Zvaifler et al ., ; Gilevich et al ., ), others failed to reproduce similar findings (Wexler et al ., ; De Felice et al ., ). Recent data suggests that although G‐CSF could increase MSCs in the BM, neither G‐CSF alone or in combination with plerixafor affects the PB mobilization of MSCs (De Felice et al , ).…”
Section: Discussionmentioning
confidence: 85%
“…However, several studies have shown that MSCs obtained from BM, AT, and other sources do express CD34 surface markers [9,[15][16][17][18]. MSCs can be seen in abundant numbers in the circulation under the following circumstances: stem cell mobilization with growth factors, tissue injuries, stroke, hypoxia, and inflammatory conditions [9,[19][20][21][22][23][24]. Despite the efforts made over the last five decades including identification of nine transcriptional factors, little is known about the molecular basis underlying the stemness of MSCs, and it is still unclear whether the recently discovered genes regulate stemness or only differentiation of MSCs [12].…”
Section: Mscsmentioning
confidence: 99%
“…Initially, there was controversy regarding the presence of MSCs in the circulation of human adults and there was an impression that BM-derived MSCs or stromal progenitor cells cannot be recovered from peripheral blood progenitor cell collections obtained from healthy donors or patients who underwent peripheral stem cell collections after mobilization [51,[53][54][55]. Later on studies have shown the following: (1) presence of small numbers of MSCs in the peripheral blood of adults in the steady state, (2) MSCs can be isolated from peripheral blood during stem cell collections or in the presence of trauma or inflammation, and (3) not only presence of MSCs among mobilized peripheral blood stem cells in the circulation but also their migration to the BM in order for them engraft at a later stage [53,[56][57][58][59]. Other studies have also shown that HSCs and progenitor cells are mobilized from the BM into the peripheral blood under the following circumstances: stem cell mobilization using chemotherapeutic agents or growth factors, tissue injuries or trauma, hypoxia, stroke and inflammatory conditions [46,52,[57][58][59][60].…”
Section: Journal Of Stem Cell Biology and Transplantationmentioning
confidence: 99%
“…Later on studies have shown the following: (1) presence of small numbers of MSCs in the peripheral blood of adults in the steady state, (2) MSCs can be isolated from peripheral blood during stem cell collections or in the presence of trauma or inflammation, and (3) not only presence of MSCs among mobilized peripheral blood stem cells in the circulation but also their migration to the BM in order for them engraft at a later stage [53,[56][57][58][59]. Other studies have also shown that HSCs and progenitor cells are mobilized from the BM into the peripheral blood under the following circumstances: stem cell mobilization using chemotherapeutic agents or growth factors, tissue injuries or trauma, hypoxia, stroke and inflammatory conditions [46,52,[57][58][59][60]. Successful transplantation of HSCs and progenitor cells is based on their ability to home to the BM and on their engraftment capacity [46].…”
Section: Journal Of Stem Cell Biology and Transplantationmentioning
confidence: 99%